Unusual Presentation of Papillary Microcarcinoma of Thyroid as Thigh Mass - Koyye Ravindranath Tagore; S. Ramineni Asok Kumar (Case Reports in Pathology)
An elderly otherwise healthy male presented with a mass in thigh. Fine needle aspiration cytology (FNAC) revealed features of papillary carcinoma of thyroid, suggesting secondary deposits. Later the patient was clinically evaluated. There was no obvious thyromegaly both clinically and sonologically. The patient was followed up. One month after initial presentation, he came with an enlarged cervical lymph node and a tiny nodule in thyroid. FNAC from both the thyroid and cervical lymph node showed identical features of papillary carcinoma.